Influence of CYP2D6-dependent metabolism on the steady-state pharmacokinetics and pharmacodynamics of metoprolol and nicardipine, alone and in combination. - Laurent-Kenesi, M A (1993)
1 The metabolism of metoprolol depends in part on the genetically determined activity of the CYP2D6 isoenzyme. In vitro studies have shown that nicardipine is a potent inhibitor of CYP2D6 activity. Since the combination of metoprolol and nicardipine is likely to be used for the treatment of hypertension, we examined the interaction between these two drugs at steady-state. 2 Fourteen healthy volunteers, seven extensive and seven poor metabolisers of dextromethorphan were studied in a double-blind, randomised cross-over four-period protocol. Subjects received nicardipine 50 mg every 12 h, metoprolol 100 mg every 12 h, a combination of both drugs and placebo during 5.5 days. Steady-state pharmacokinetics of nicardipine and metoprolol were analyzed. Beta-adrenoceptor blockade was assessed as the reduction of exercise-induced tachycardia. 3 During treatment with metoprolol, alone or in combination with nicardipine, its steady-state plasma concentrations were higher in subjects of the poor metaboliser phenotype than in extensive metabolisers. Beta-adrenoceptor blockade was also more pronounced in poor metabolisers than in extensive metabolisers of dextromethorphan during treatment with metoprolol alone or in combination with nicardipine (24.0 +/- 2.4% vs 17.1 +/- 3.5% and 24.1 +/- 2.5% vs 15.4 +/- 2.7% reduction in exercise trachycardia, respectively, P < 0.01 in each case). 4 Nicardipine produced a small increase in plasma metoprolol concentration in extensive metabolisers from 35.9 +/- 16.6 to 45.8 +/- 15.4 ng ml(-1) (P < 0.02), but had no significant effect in poor metabolisers. However, nicardipine did not alter the R/S metoprolol ratio in plasma 3 h after dosing, the plasma concentration of S-(-)-metoprolol 3 h after dosing or the beta-adrenoceptor blockade produced by metoprolol in subjects of both phenotypes. The partial metabolic clearance of metoprolol to alpha-hydroxy-metoprolol was not altered significantly in extensive metabolisers. Plasma nicardipine concentration and beta-adrenoceptor blocking effects did not differ between the phenotypes and were not influenced by metoprolol. We conclude that beta-adrenoceptor blockade during repeated dosing with metoprolol is more pronounced in poor than in extensive metaboliser subjects, that nicardipine decreases a CYP2D6-independent route of metoprolol elimination but does not increase beta-adrenoceptor blockade during repeated dosing with metoprolol.